PERAN KEWIRAUSAHAAN DALAM PENDIDIKAN - Safroni Isrososiawan (SOCIETY, 2013)
In its growth cultiviation values of entrepreneurship not only among the entrepreneurs and business area but it has expended into the education world, where its activity also strongly need the soul of entrepreneurship. Entrepreneurship in education has aim for human being holistically, as mankind owning character, understanding and skills as entrepreneur. Basically the educators of entrepreneurship conducted by headmaster, teacher and educators (counselor), educators definitely as a education community. The educators of entrepreneurship applied into curriculum by identifying some type of school activities at school which can realize the education of entrepreneurship it self and also for their students in everyday of life. In this case, the program of education entrepreneurship at school could internalized through various aspects which integrated in all subject of entrepreneurship education of entrepreneurship which integrated in extra curricular, entrepreneurship through self development, change of execution of study Entrepreneurship from practice to theory, integration of education Entrepreneurship into book guidance, integration of education Entrepreneurship through school culture, integration of education Entrepreneurship through local subject.